Alkene epoxidation with iodosylbenzene catalysed by polyionic manganese porphyrins electrostatically bound to counter-charged supports - Sacco, H. C.; Iamamoto, Y.; Smith, JRL (Royal Soc Chemistry, 2001)
Manganese(III) complexes of tetra-anionic and tetra-cationic porphyrins have been immobilised on counter-charged, surface-modified silica supports and on organic ion-exchange resins. The reactions of these supported manganese(III) porphyrin systems and analogous uncharged homogeneous systems have been examined using cyclooctene and (E)- and (Z)-4- methylpent-2-ene epoxidations, with iodosylbenzene (PhIO) as the oxygen donor.Comparisons using the manganese porphyrin systems as catalysts for the epoxidation of cyclooctene in acetonitrile reveal that, in low turnover reactions (maximum 136 turnovers), they all give an essentially quantitative yield of epoxide although the heterogeneous reactions are significantly slower than the homogeneous analogues. In large scale repeat-use experiments, however, the supported catalysts are clearly superior, giving markedly better yields.The epoxidations of (E)- and (Z)-4- methylpent-2-ene with all the catalysts show a very high stereoretention, with the (Z)-alkene reacting faster than the (E)-isomer. The sterically hindered manganese(III) 5,10,15,20-tetrakis(2,6-dichloro-3-sulfonatophenyl)porphyrin (MnTDCSPP) shows the highest selectivity for the (Z)-isomer; by contrast the supported manganese(III) 5,10,15,20-tetrakis[2,3,5,6-tetrafluoro-4-(trimethylammonio)phenyl]porphyrin on Dowex (MnTF(4)TMAPP-Dowex) reacts with the two alkenes at effectively the same rate.The mechanism of the epoxidations and the influence of the porphyrin ligand and support on the substrate selectivity are discussed.